Chapter 2 Making of museums - Kulshreshtha, Salila (Taylor & Francis, 2018)
The chapter discusses the shift in the focus of the Archaeological Survey of India from excavation and documentation to preservation and conservation of sites and artefacts. The chapter then highlights the fate of two private collections from Bihar: the images in the Bodh Gaya Mahant's compound and those which belonged to AM Broadley's Bihar Museum. In the process of rediscovery while some images continued to be worshipped, a large number of these were moved into museums. The scene of actions moves to the newly constituted Museums such as the Patna Museum and the Nalanda Museum and investigates how the narratives of display, cataloguing and nomenclature presented a visual archive which codified the parameters within which religious images came to be viewed.